How can bullying affect body image? A systematic review to understand the relationship between bul-lying, body image and eating disorders - María Martínez López; Pedro Gil-Madrona; Carlos Montoya-Fernández; Isabel María Gómez-Barreto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Nowadays bullying has become one of the biggest challenges faced by teachers all around the world due to the consequences it has on the victims in the long and short term. The most common consequences expressed by bullying victims are anxiety, depression, socialization problems, lower self-esteem, and a negative perception of their body image. The negative perfection of body image has a very strong relationship with the development of eating disorders. Due to this fact, it is crucial to study the relationship that bullying and eating disorders might have. By using PRISMA model (Page et al., 2021) a systematic review to prove this relationship has been developed. After searching and analyzing different articles, the included sample and the instruments used, it was possible to conclude that being a victim of bullying is related with developing an eating disorder. For this reason, it is crucial to create prevention programs at schools that help teachers, parents and the different professionals to face both problems as it is essential to keep students safe inside and outside the classroom.